2022
DOI: 10.1039/d2tb01890j
|View full text |Cite
|
Sign up to set email alerts
|

High fibroin-loaded silk-PCL electrospun fiber with core–shell morphology promotes epithelialization with accelerated wound healing

Abstract: Silk fibroin (SF) is a widely explored biopolymer for wound healing applications due to the presence of amino acids in the biodegradable polymer chain with superior mechanical properties. Herein, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Moreover, these kinks are more prominent in the wet stent samples indicating delamination among the layers as a result of different extent of swelling of electrospun layers and 3D printed layers. The abovementioned reported mechanical property of the stents was associated with the β sheet formation from the random coil owing to methanol treatment . Notably, experimental data of cervical tissue by Callejas et al, 2020 showed non-linear elastic behavior with differential shear modulus of 1.29 ± 0.15 and 3.60 ± 0.63 MPa for the epithelial layer and connective layer of the cervix, respectively …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, these kinks are more prominent in the wet stent samples indicating delamination among the layers as a result of different extent of swelling of electrospun layers and 3D printed layers. The abovementioned reported mechanical property of the stents was associated with the β sheet formation from the random coil owing to methanol treatment . Notably, experimental data of cervical tissue by Callejas et al, 2020 showed non-linear elastic behavior with differential shear modulus of 1.29 ± 0.15 and 3.60 ± 0.63 MPa for the epithelial layer and connective layer of the cervix, respectively …”
Section: Resultsmentioning
confidence: 95%
“…The abovementioned reported mechanical property of the stents was associated with the β sheet formation from the random coil owing to methanol treatment. 50…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…These results indicated that the core–shell fibers can inhibit the burst release phenomenon and effectively prolong the release time of pheromones in the fibers. The ability of core–shell fibers to improve the release behavior of loaded active ingredients has been reported in the field of drug carriers . From the release mechanism of Figure c, unlike TDDA dispersed in monoaxial fibers, the drug-loading system constructed by core–shell fibers concentrated TDDA in the PCL core layer.…”
mentioning
confidence: 90%
“…The ability of core−shell fibers to improve the release behavior of loaded active ingredients has been reported in the field of drug carriers. 48 From the release mechanism of Figure 4c, unlike TDDA dispersed in monoaxial fibers, the drug-loading system constructed by core−shell fibers concentrated TDDA in the PCL core layer. This structure improved the burst release caused by uneven dispersion of TDDA.…”
Section: T H Imentioning
confidence: 99%
“…17,22,23 The electrospun nanofiber scaffolds contained sufficient voids to facilitate the exchange of moisture with the external environment, while simultaneously inhibiting bacterial infiltration and effectively reducing the risk of infections. 24,25 The unique structures of electrospun nanofibers allow them to demonstrate novel functional properties. 26−28 Consequently, electrospun nanofiber scaffolds exhibit biological activity and accelerated skin healing.…”
Section: Introductionmentioning
confidence: 99%